Pengembangan Permainan Kosakata Interaktif Bahasa Jerman Level A1 Berbasis Aplikasi Construct 3 - Onyx Nifty; Elfretty Sitanggang; Yuni Melati Anestasya Simaremare; Roihan Anwar; Surya Yusuf; Surya Masniari Hutagalung (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to create Student Worksheets (LKS) using the Construct 3 application as a German vocabulary learning media at the A1 level for high school students. This study will employ a descriptive qualitative method. The process of creating the LKS utilizes Richey and Klein's theory, involving the following phases: (1) the planning phase, (2) the development or creation phase, and (3) evaluation phase. The data for this research consist of German vocabulary with themes